Hubungan antara Relasi dalam Keluarga dan Kesejahteraan Subjektif Remaja Korban Perundungan Siber - Nuha Dzakiyyah; Ihsana Sabriani Borualogo; Tia Inayatillah (UPT Publikasi Ilmiah Unisba, 2025)
Abstract. Cyberbullying is increasing and negatively impacts adolescents' subjective well-being (SWB). Victims of cyberbullying often experience disruptions in interpersonal satisfaction, especially within family relationships. Family relationships, which involve social interactions and closeness among members, are essential for fostering satisfaction and happiness. This study examines how family relationships contribute to the SWB of junior high school students in Bandung City who experience cyberbullying. Participants included 239 students aged 12–16 years (N= 239; 51.6% female; 49.0% male) selected through stratified cluster random sampling in a cross-sectional survey. Family relationships were measured using the Children's World's tool and SWB was measured using the Children's Worlds Subjective Well-Being Scale (CW-SWBS5). Victim categorization followed Patchin and Hinduja’s measurement instrument. Data analysis using linear regression techniques. Results showed that victims of cyberbullying had below-average SWB (M = 64.9; SD = 28.7) compared to Cummins’ theoretical mean of 75, with female victims reporting lower SWB than males. Family relationships, such as feeling safe at home (β = .349, p < .001) and parents listening and paying attention (β = .220, p < .011), significantly positively contributed to their SWB. Therefore, building positive family relationships and interactions is crucial for enhancing the SWB of adolescent victims of cyberbullying. Abstrak. Perundungan siber semakin meningkat dan berdampak negatif pada kesejahteraan subjektif remaja. Korban sering kali mengalami gangguan dalam kepuasan interpersonal, terutama dalam hubungan keluarga. Hubungan keluarga, melibatkan interaksi sosial dan kedekatan antara anggota, sangat penting untuk menumbuhkan kepuasan dan kebahagiaan. Penelitian ini meneliti bagaimana hubungan keluarga berkontribusi terhadap SWB siswa SMP di Kota Bandung yang mengalami perundungan siber. Partisipan terdiri dari 239 siswa berusia 12-16 tahun (N= 239; 51.6% perempuan; 49.0% laki-laki) yang dipilih melalui stratified cluster random sampling dalam survei cross-sectional. Hubungan keluarga diukur dengan menggunakan alat Children's World’s dan SWB diukur dengan menggunakan Children's Worlds Subjective Well-Being Scale (CW-SWBS5). Kategorisasi korban berdasarkan instrumen pengukuran Patchin dan Hinduja. Analisis data menggunakan teknik regresi linier. Hasil penelitian menunjukkan bahwa korban memiliki kesejahteraan subjektif di bawah rata-rata (M = 64,9; SD = 28,7) dibandingkan dengan rata-rata teoritis Cummins yaitu 75, dengan korban perempuan melaporkan kesejahteraan subjektif yang lebih rendah dibandingkan laki-laki. Hubungan keluarga, seperti merasa aman di rumah (β = .349, p <.001) dan orang tua yang mendengarkan dan memberi perhatian (β = .220, p <.011), secara signifikan memberikan kontribusi positif terhadap kesejahteraan subjektif mereka. Oleh karena itu, membangun hubungan dan interaksi keluarga yang positif sangat penting untuk meningkatkan kesejahteraan subjektif korban.